(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Water toxicity is a research to research the influence on the health of fish and other aquatic species of environmental pollutants, especially pesticides and insecticides. Compounds for the management of insect, aquatic weed and vegetable conditions are pesticides. Pesticide. Residues of pesticides enter the water through surface runoff, which pose a danger to aquatic flora and wildlife, with fish being one of the most susceptible in the food chain. Agriculture, forestry, public health and veterinary care utilize large numbers of pesticides. Application is meant to classify pesticides. The three main pesticides are herbicides (weed control), insecticides (insect monitoring), and fungicides however they have the most acute toxicity. Since fish are an important source for humans and household animals of proteins and lipids, the health of fish is vital for human health. Insecticides are chemicals used to control insects, killing or preventing the insects from taking part in unwanted or harmful behavior. Pesticide contamination of surface water is widely known to have an adverse effect on the growth, survival and reproduction of fish. th study of the impact on the health of fish and seafood of water pollution Fish Pesticides Toxicity Pesticide in India The benefits and disadvantages of plagues, the effects of pesticides, and the impact of insecticides on various fish parameters.